Analisis Penguasaan Teknik Dasar Bermain Bola Voli Pada Mahasiswa Prodi Penjas Melalui Modifikasi Permainan Bola Voli Tanpa Net Angkatan 2022 Universitas PGRI Adi Buana Surabaya - Muhammad Muhyi; I Gede Darma Utamayasa (YLPK Mahardhika, 2023)
The purpose of this study was to analyze the level of mastery of the basic skills of playing volleyball in students of the Physical Education study program class of 2022 at PGRI Adi Buana University, Surabaya. The basic skills of playing volleyball include the basic techniques of passing, blocking, serving, and smashing. The research method uses a quantitative descriptive, the number of samples is 80 students of the Physical Education study program class of 2022 class C and D. The research location of the Adi Buana PGRI University Surabaya campus, data collection techniques through observation, and quantitative descriptive data analysis techniques. The results showed that students who were given basic volleyball playing activities without a net showed better mastery of basic volleyball skills, where the average score was 70. The conclusion of this study is that mastery of the basic skills of playing volleyball can be improved by playing volleyball without a net.